Shedding and genetic diversity of Leptospira spp. from urban stray dogs in Klang Valley, Malaysia - Goh, Soon Heng; Khor, Kuan Hua; Radzi, Rozanaliza; Lau, Seng Fong; Bejo, Siti Khairani; Abdul Rahman, Mohammad Sabri; Roslan, Mohd Azri (Elsevier, 2021)
Leptospirosis is an endemic zoonoses of global proportions. Stray dogs have been postulated to play a role in disease transmission; however, supporting information are still limited. Roaming behavior may not only predispose the dogs to infection, but could also contribute to disease spread. In this study, the susceptibility of urban stray dogs in shedding Leptospira spp. was determined. Blood, urine, and tissue samples of kidney and liver were collected from 100 dogs from 2 animal control facilities. Serological testing using microscopic agglutination test (MAT) were performed on blood against 20 leptospiral serovars with a cut-off titre of ≥ 1:100. Samples were cultured onto semi-solid Ellinghausen and McCullough modified by Johnson and Harris (EMJH) media. Isolates were identified using molecular polymerase chain reaction (PCR) using 2 primers (16s rRNA and LipL32) and hyperimmune serum (HIS) MAT. The seroprevalence for the dogs positive for leptospirosis was 32% (n=32/100) with the following detected serovars: Javanica (n=13), Bataviae (n=10), Icterohaemorrhagiae (n=3), Autumnalis (n=2), Canicola (n=1), Pyrogenes (n=1), Copenhageni (n=1), and Australis (n=1). Six Leptospira spp. isolated were procured from urine (n=2), kidney (n=2) and liver (n=2). All 6 isolates belonged to L. interrogans, a pathogenic variant of Leptospira spp. Serotyping and phylogenetic analysis suggested serovar Bataviae (n=5) and serovar Canicola (n=1). Presence of vaccinal serovars (Icterohaemorrhagiae and Canicola) suggested potential post-vaccination antibodies but the predominance of non-vaccinal serovars (Javanica and Bataviae) indicate the possibility of current infection or post-exposure. Isolation of Leptospira spp. directly from urine sample not only suggested an active infection but highlighted the potential shedding capability among these stray dogs. These findings further strengthen speculations that urban stray dogs could play a role in transmission and dissemination of leptospirosis through their constant movement. The urine of infected dogs may contaminate the environment, posing a major public health threat.